Entre Juan Moreira y Osvaldo Dragún. : mito, parodia y teatro popluar. - Saura Clares, Alba (Latin American Theatre Review, 2022)
This paper focuses on one of the most relevant plays in the history of Argentinian theater: Juan Moreira (1884/1886), in his premiere by the Hermanos Podestá. This paper aims to explore the reasons for the canonization of the play, considered to be at the core of the origin of Argentinian theatre and the national idea of theatre, both because of its text and its performance, at the time that analyses its legacy throughout the twentieth century. Then, the paper moves to analyse the interesting parody version of the play, Hoy se comen al flaco (1977/1983), in which the Argentinian playwright Osvaldo Dragún, in the context of the last dictatorship in the country, reflects on the theatrical tradition and the sociopolitical situation of Argentina through Juan Moreira.